Implementation of Information Technology (IT) at The Impact of The Covid-19 Pandemi in The Islamic Boarding School (Survey) - Syauqie Muhammad Marier; Pipit Febriana Dewi; Dewi Lestari (Fakultas Teknik Universitas Wahid Hasyim, 2022)
Islamic boarding schools are the original Indonesian Islamic education institution with traditional culture. The existence of a Covid-19 pandemic resulted in school learning policies and boarding schools using the online method. It is conducted to break the chain of spread of the Covid-19 virus. It has an impact on various activities in Islamic boarding schools and on the need to use information technology (IT). Research was used for an initial mapping of the implementation of IT in Islamic boarding schools. The study aimed to determine to what extent IT adoption was in the Islamic boarding school in the Special Region of Yogyakarta. The method used is a survey with descriptive analysis. The survey was carried out on the board of Islamic boarding schools. The questionnaire contained the identification of the types of Islamic boarding schools and four variables related to IT implementation in Islamic boarding schools. The four variables are application information/ information systems used by Islamic boarding schools, from where Islamic boarding schools obtain information systems, existing system integration, and Android-based applications. The results obtained were that 88.9% of the 58 Islamic boarding schools already had an information system. Islamic boarding schools have a diverse information system, such as the new student admission, boarding school information systems, school information systems, monitoring systems, financial systems, and administrative systems. There are 44.2% of the system which has integrated data and functionality and 59.5% systems based on Android. The average Islamic boarding school that applies to IT is a boarding school with some students (santri) of more than 400, and the category is a modern salafiah Islamic boarding school. The challenges facing Islamic boarding schools in IT implementation are the lack of human resources, infrastructure limitations, and the lack of socialization of information systems in the guardian of students.